Early school leaving: obstetrical and neonatal risks - Rajaonarivony, Marie Valerie; Ratsiatosika, Tanoja A.; Randriamahavonjy, Romuald; Rainibarijaona, Lantonirina; Fanomezantsoa, Jean Eustache; Andriamiandrisoa, Aristide; Randaoharison, Pierana Gabriel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Introduction: Maternal mortality remains very high in Madagascar. In addition, women's education level is low. The aim of this study is to determine the impact of the maternal educational level on the obstetrical and neonatal outcomes. Methods: This is a retrospective analytical study of primiparae with seven years of study or less to patients with more than seven years of study at Zafisaona Gabriel Mahajanga university hospital center. Results: Prematurity was higher in low-grade patients (RR=2.6 (1.04-6.51)), and low birth weight was the leading cause of neonatal morbidity (RR=3.52). Pregnancy screening, maternal morbimortality, caesarean section, neonatal death and fetal intrauterine death were identical between the two groups. Conclusions: Education has a positive impact on maternal health. An education on pregnancy outcomes should be done at school.